Implementation of A Traceability System for Canned Fish Products using The FMECA Approach - Berliana, Jihan Nisrinah; Hariono, Budi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
PT. XYZ is a company that operating in the canned fish processing sector. In implementing the traceability system, traceback product still experiences obstacles so it cannot be implemented properly in the Company. This research was conducted to determine the traceability critical point which is a weakness of the traceability system being implemented. The method used is the FMECA (Failure Modes, Effects, and Criticality Analysis) approach, which is a development of the FMEA (Failure Mode Effect Analysis) method with the inclusion of the CA (Criticality Analysis) method to evaluate the effective level and efficiency of the traceability system being implemented. The results of the analysis showed that 43 possible failure points were identified, of which 2 points were in the unacceptable area, 3 points were in the undesirable area, 12 points were in the acceptable with revision area, and 26 points were in the acceptable without revision area. Traceability of canned fish products at fish canning companies has been going well with 5 critical points of traceability, namely the absence of information on the origin of the fish, not providing special coding for each fish received, not carrying out microbiological testing on the fish received, each fish received is not differentiated. The storage location is between each supplier, and no special records are made at the draining stage. Keywords: Critical analysis, Failure, FMECA, Traceability, Quality assurance.